A Silver Age? The German Economy since Reunification. Issue 4 (1st December 2019) - Silvia, Stephen J.
Abstract : Since German unification, assessments of the German economy have swung from "sick man of the euro" in the early years to dominant hegemon of late. I argue that the German economy appears strong because of its recent positive performance in two politically salient areas: unemployment and the current account. A deeper assessment reveals, however, that German economic performance cannot be considered a second economic miracle, but is at best a mini miracle. The reduction in unemployment is an important achievement. That said, it was not the product of faster growth, but of sharing the same volume of work among more individuals. Germany's current account surpluses are as much the result of weak domestic demand as of export prowess. Germany has also logged middling performances in recent years regarding growth, investment, productivity, and compensation. The article also reviews seven challenges Germany has faced since unification: financial transfers from west to east, the global financial crisis, the euro crisis, internal and external migration, demographics, climate change, and upheavals in the automobile industry. German policy-makers managed the first four challenges largely successfully. The latter three will be more difficult to tackle in the future.